Midnight Express. - Hayes, Billy; Hoffer William . (New York E. P. Dutton, 1977)
One of the best-known books on doing time in a foreign prison, Midnight Express earned almost instant cult status when it was released in 1977. Hayes story is dramatic and spawned plenty of spinoffs a movie and even a ballet and while many people think they know what happened to Hayes in that Turkish prison, you have to go back to the book for the truth.
Keywords: Literature